Digitalisation of the building permit process - a case study in Italy. Issue 5 (1st November 2022) - Fauth, J; Malacarne, G; Marcher, C
Abstract: Building permitting plays a significant role in a building's life cycle because without a building permit a legal construction fails. However, digitalization in building permit authorities is rare in global context and issuing a building permit is still mostly a manual and time-consuming process. Moreover, a gentle instrument that authorities do not feel overwhelmed with is missing so far. Hence, a BIM-oriented and process-based web application prototype was developed in preliminary research. This research aims at validating and testing the BIM-oriented and process-based web application prototype by analysing the building permit processes in relation to digitalization and promotion of BIM usage by means of a specific case study. For this purpose, an empirical study using qualitative expert interviews in a building permit authority in South Tyrol (Italy) is conducted. The results shed light on the level of acceptance and plausibility of the web application prototype, as well as the ability of the prototype to assist building permit authorities within their review process.